BIOEKOLOGI Grapevine leafroll-Associated Virus type 3 (GLRAV-3) PENYEBAB PENYAKIT DAUN MENGGULUNG PADA TANAMAN ANGGUR (Vitis vinifera L.) - Yuyun Fitriani; I Gede Rai Maya Temaja; G. N. Alit Susanta Wirya (Journal of Agricultural Science and Biotechnology, 2018)
The survey of vineyard fields in Buleleng, Bali, Indonesia was conducted, some grapevine cultivars were found had grapevine leaf roll disease symptomps. The symptoms including interveinal reddening or yelowing and fall leaves, down rolling of leaves, phloem disruption, and the fruit maturation is delayed. The analysis of enzyme linked immunosorbent assay (ELISA) of symptom leaf with Grapevine leaf roll-associated virus type 3 (GLRaV-3) antiserum shown the disease was corresponding to the GLRaV-3. The study was conducted to identify the mealybug that colonized of grapevine, to determine capability of mealybug to transmitted GLRaV-3 and host range GLRaV-3.Base on the survey ofmealybuginvineyard fields in Buleleng, Bali, the two types of mealybug were identified, namely Ferrisia virgata (Ckll.) (Hemiptera: Pseudococcidae) and Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae). Results of the transmission test showed that only M. Hirsutus are capable of transmitting GLRaV-3. The plant range host test of GLRaV-3 inoculation with M. hirsutuswas conducted and the symptom was detected on3plants species, grapevines (Vitis vinifera), native gooseberry (Physalis floridana) andshoe flower (Hibiscus rosa-sinensis) from18 species of plants that used.